STRATEGI KEGIATAN STUDENT LANGUAGE FESTIVAL (SLF) DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB PADA SISWA AL AZHAR IIBS - Sitta Subekti (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
Arabic is one of the essential languages within the context of Islamic education. However, student motivation to learn the language is often low due to the perception that Arabic is a difficult subject, coupled with learning methods that lack variety and tend to be conventional. This low motivation results in a lack of active participation, interest, and confidence among students in using Arabic orally. Therefore, a method capable of increasing motivation for learning Arabic is required. This study aims to enhance student motivation in learning Arabic through the Student Language Festival (SLF) using a creative and competitive approach. This study employs a qualitative approach using observation, interviews, and documentation techniques. The respondents of this research are Al Azhar IIBS students participating in SLF activities. The data obtained were analyzed using descriptive triangulation methods to determine the increase in student motivation. The results show that SLF strategies including creative content preparation, inter-class competitions, and digital technology integration significantly increased students' intrinsic motivation through enjoyable and collaborative learning experiences. Students reported an increase in self-confidence and a sustained interest in the Arabic language. Based on these findings, it can be concluded that SLF activities can enhance students' learning motivation in Arabic and can serve as an innovative and interactive alternative learning strategy.